If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + 7a + -4a = 0 Combine like terms: 3a + 7a = 10a 10a + -4a = 0 Combine like terms: 10a + -4a = 6a 6a = 0 Solving 6a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Divide each side by '6'. a = 0 Simplifying a = 0
| 2(a-8)=80 | | 26=4a-22 | | 12a-25=35 | | 4(3x-1)-2x=56 | | 50=7a-6 | | 7x+1250=1264 | | 21+9a=66 | | 3e^-(t/0.48) | | 236x-1888=0 | | x+(x+30500)=190500 | | 5-(3x)=0 | | 5-(3-x)=5 | | 2(x+5)+8= | | 4(3+h)-2(5+3h)= | | -3(y/1)= | | 27x^2+42x-9=0 | | ln(7-x)-ln(3x-1)=1 | | 35-3x=7-10x | | 3/9x | | 4x+9=31-6x | | 6x+-1(-x)=3x+8 | | 4x*5y*2z= | | ln(x+1)+lnx=2 | | 6k+1+5k= | | (3ad/4cd)^-2 | | 2+9x=4x-13 | | x+y+3xy=2015 | | 4a-9b= | | 4z/9-2=0 | | 7x+10y=300 | | (1-w)(5w-6)=0 | | y(y-1)=20 |